Performance Comparison of Static and Rotating Bioreactor for Bacterial Cellulose Production from Tofu Wastewater - Choerudin; Dadi Arif Viliando; Dyah Setyo Pertiwi (Journal of Chemical Process Engineering, 2026)
Tofu industry wastewater is a potential substrate for bacterial cellulose (BC) production due to its residual nutrient content. However, conventional static culture has limited oxygen transfer and substrate diffusion, resulting in low substrate utilization efficiency. This study presents a comparative evaluation of static and rotating bioreactor (RB) systems, with a primary focus on substrate utilization, bacterial growth, and BC yield. In addition, the effect of inoculum volume (10% and 30%) was investigated to assess its influence on process performance. The results demonstrate that the RB system significantly outperforms static culture, achieving 1.6 – 2 times higher substrate utilization and 53.3 - 61.3% higher BC yield on initial substrate. The highest BC product is 5 g dry mass BC/ L medium in the RB system.   Furthermore, the RB system enhances substrate conversion toward bacterial growth, indicating improved metabolic efficiency under dynamic conditions. A lower inoculum volume, 10% inoculum with 1-10 million CFU/mL, resulted in better overall performance compared to 30% inoculum, suggesting that excessive inoculum does not improve process efficiency. These findings confirm that the rotating bioreactor is a more effective system for intensifying BC production, particularly in terms of substrate utilization, and highlight its potential for scalable and sustainable bioprocess applications.